Prevalence of shoulder and upper-limb disorders among workers in the fish-processing industry. - Chiang, H. C.; Ko, Y. C.; Chen, S. S.; Yu, H. S.; Wu, T. N.; Chang, P. Y. (Scandinavian Journal of Work, Environment & Health, 1993)
A cross-sectional study was conducted among fish-processing workers to evaluate the prevalence of shoulder and upper-limb discomforts and to assess the associated ergonomic risk factors. A prestructured interview, a medical check-up, and job analyses were performed to determine musculoskeletal disorders among 207 workers in eight factories. The results showed shoulder girdle pain (30.9%), epicondylitis (14.5%), and carpal tunnel syndrome (15.0%) as the three most common soft-tissue disorders. The odds ratio of shoulder girdle pain was 1.6 (95% CI 1.1-2.5) among the workers who performed tasks with repetitive movement of their upper limbs, while it was 1.8 (95% CI 1.2-2.5) for the workers who sustained forceful movement of their upper limbs during work. Women taking oral contraceptives had a 2.0 times higher odds ratio for carpal tunnel syndrome than did other women. It would appear that untrained or unskilled workers were prone to suffer from musculoskeletal disorders.